1998
DOI: 10.1023/a:1006951423251
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We have explored two aspects of internal capsule development that have not been described previously, namely, the development of glia and of blood vessels. To these ends, we used antibodies to glial fibrillary acidic protein (GFAP) and to vimentin (to identify astrocytes and to radial glia) and Griffonia simplicifolia (lectin; to identify microglia and blood vessels). Further, we made intracardiac injections of Evans Blue to examine the permeability of this dye in the vessels of the internal capsule during neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…First, blood vessels and blood circulation might regulate microglial migration in the developing brain. Microglial distribution in the brain parenchyma coincides with vascularization, which occurs at E10 in mice (Earle and Mitrofanis 1998 ). Consistent with this finding, another study reported that microglia reached the area surrounding the spinal cord via the developing vasculature and then proliferated (Rigato et al 2011 ).…”
Section: Distribution and Migration Of Microglia In The Developing Cerebral Cortexmentioning
confidence: 99%
See 1 more Smart Citation
“…First, blood vessels and blood circulation might regulate microglial migration in the developing brain. Microglial distribution in the brain parenchyma coincides with vascularization, which occurs at E10 in mice (Earle and Mitrofanis 1998 ). Consistent with this finding, another study reported that microglia reached the area surrounding the spinal cord via the developing vasculature and then proliferated (Rigato et al 2011 ).…”
Section: Distribution and Migration Of Microglia In The Developing Cerebral Cortexmentioning
confidence: 99%
“…The first way is through blood vessels. An early study reported that microglia colonize the embryonic brain in accordance with vascularization (Earle and Mitrofanis 1998 ). A study on microglial origins using Ncx1 −/− mice, in which heartbeat and blood circulation are impaired due to deficiencies in Na + /Ca 2+ exchangers, confirmed that microglial precursors could not invade the brain parenchyma, indicating that these cells enter the embryonic brain in a manner dependent on the establishment of blood circulation (Ginhoux et al 2010 ).…”
Section: Entry Of Microglia Into the Brain Parenchymamentioning
confidence: 99%
“…These precursor cells were found in the vicinity of brain capillaries and characterized by a round or irregularly shaped cell body, with or without pseudopodia [98]. The colonization of the brain by microglia was observed to coincide with CNS vascularization during embryonic development [99,100]. In the fetal human brain microglia were located at highly vascularized sites at between 16-and 22-weeks gestation [101].…”
Section: Microglia and Vascularizationmentioning
confidence: 99%